Side effects of drugs annual. - Ray, Sidhartha D. (ISSN, 2022)
Side Effects of Drugs Annual: A Worldwide Yearly Survey of New Data in Adverse Drug Reactions, Volume 44, first published in 1977, presents clinicians and medical investigators with a critical survey of new data and trends in adverse drug reactions and interactions. Topics covered in this new release include Thyroid hormones, Iodine and Iodides, and Antithyroid Drugs, Side Effects of Antidepressant Medications, Side Effects of Lithium, Side Effects of Opioid Analgesics and Narcotic Antagonists, Side Effects of Beta-lactams and Tetracyclines, Side effects of Anti-diabetic Drugs, Vaccines, Side Effects of Neuromuscular Blockings Agents and Skeletal Muscle Relaxants, and much more. Other chapters cover General Anesthetics and Therapeutic Gases, Drugs that Act on the Respiratory Tract, Positive Inotropic Drugs and Drugs Used in Dysrhythmias, Metals and Metal Antagonists, Antiseptic Drugs and Disinfectants with special scrutiny of COVID-19 pandemic related side effects, Drugs in tuberculosis and leprosy, Anthelminthic drugs, Blood and blood treatments, and a variety of other topics.